Design considerations, modelling, and control of dual‐active full bridge for electric vehicles charging applications. Issue 12 (28th October 2019) - Jarraya, Fatma; Khan, Ahmad; Gastli, Adel; Ben‐Brahim, Lazhar; Hamila, Ridha
Abstract : The dual active full bridge (DAFB) is one of the promising isolated DC/DC converter topologies that will play a significant role in the future of electric vehicle (EV) integration in smart grids (SGs). This is due to its inherent soft switching and control simplicity. Therefore, this study presents first the latest developments related to the design of DAFB converter in EV charging technology. It provides a brief discussion of the crucial recommendations regarding the reliability, efficiency, system configuration, EV charger control scheme, battery lifetime, and system materials. Then, it presents a step‐by‐step modelling approach for a non‐ideal DAFB for the purpose of designing its controller. In addition, the model provided by this study includes all non‐idealities due to the high‐frequency (HF) transformer, semiconductor switches, passive components, and digital system delays. Eventually, the proposed system design and analysis was validated by implementing a 6.1 kW prototype on Simulink and Typhoon‐HIL real‐time simulator.